Evolution of the classification of flammable and combustible liquids in Russia. Issue 2 (4th December 2017) - Alexeev, Sergey; Smirnov, Vitaly; Barbin, Nicolay; Alexeeva, Dar'ya
Abstract : Classification of liquids on the basis of the fire and explosion characteristics plays an important role to ensure fire safety. The history of this classification is closely connected with oil revolution that took place in the second half of the 19th century in USA. Cheap kerosene led to the beginning of kerosene era. The increase of fires and explosions was the by‐effect of that process and became a real problem for a lot of countries. For safe kerosene in Russia, the first limits were set in 1886 and 1889 by the decree of the Russian Emperor Alexander III. In the future, this classification has been extended to all liquids. The first Soviet classification appeared in 1939. After the World War II, it has been further developed. Now in Russia there are several classifications of flammable and combustible liquids, in which there is the ideology of the criteria of safe kerosene. © 2017 American Institute of Chemical Engineers Process Saf Prog 37: 230–236, 2018